Hybrid multilayered perceptron network for classification of bundle branch blocks - Megat Syahirul Amin, Megat Ali; Ahmad Nasrul, Norali; Aisyah Hartini, Jahidin (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/